Pengaruh E-service Quality Dan Harga Terhadap Keputusan Pembelian Layanan Berlangganan Streaming Music Pada Spotify - Ragana, Shalana Hardja; Arianti, Maya (eProceedings of Management, 2024)
this research is Spotify, which offers songs, podcasts, and audiobooks, and has over 200 million paid subscribers.Although Spotify's prices are higher compared to other platforms, users are expected to receive satisfactioncommensurate with the price they pay based on the quality of the service. E-service quality encompasses all customerinteractions on the website. The aim of this study is to explore respondents' perceptions of service quality, pricing,and purchase decisions regarding Spotify's music streaming service. This research also aims to determine whetherservice quality and pricing influence consumer purchase decisions for Spotify, despite frequent service interruptions.This study is quantitative with a descriptive approach. Data was collected through surveys with questionnaires filledout by respondents. The population and sample of this study consist of individuals who have purchased Spotify serviceswith various professions in Indonesia, without population limitations. A non-probability sampling technique withpurposive sampling was used, resulting in 100 respondents. The results of the study show that 76.7% of the purchasedecision variable is influenced by e-service quality and price, while the remaining 23.3% is influenced by other factorsnot included in this analysis. Keywords-e-service quality, price, purchase decision, streaming music.